EVALUASI KEBIJAKAN PEMERINTAHAN KOTA PEKANBARU TENTANG MASJID PARIPURNA. STUDI KASUS: MASJID PARIPURNA AL-UKHUWAH KELURAHAN AIR PUTIH TAHUN 2018 - Imerda Rumaigha Uwi Yuka; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Plenary Mosque is a mosque that completes all aspects on the basis that it refers to standardization and has good management governance, adequate facilities and a center for religious activities. The Plenary Mosque as a pilot mosque in order to achieve the Vision of Pekanbaru City to become a civilized Metropolitan City. The Plenary Mosque is a strategic program of the Pekanbaru City Government in realizing the Pekanbaru Smart City Madani. There are three aspects that constitute the criteria for a mosque to be called plenary, namely Idarah, Imarah, and Ri'ayah.This study aims to determine the evaluation of the Pekanbaru City Government's policy in implementing the Plenary Mosque program in Pekanbaru City in 2018. The type of research used in this study is a descriptive research type with a qualitative research approach. The types of research data are primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative data analysis.Based on the results of the study, it shows that the policy evaluation carried out by the Pekanbaru City Government at the Al-Ukhuwah Plenary Mosque in Pekanbaru City has not been implemented well enough, especially in the field of human resources and facilities that still need to be improved as well as more programs that can be formed and managed again with the aim of development of the mosque with the category of Plenary. Keywords: Government Policy, Pekanbaru City Plenary Mosque